Temporary Disenfranchisement Revisited: A Report from the 2023 Montréal Replication Games on the Robustness of Recent Findings in the APSR - Joris Frese; Alexandros Christos Gkotinakos; Pau Grau; Matthew Hepplewhite (Institute for Replication (I4R), 2023)
Leininger et al. (2023) study the political consequences of temporary disenfranchisement. Taking advantage of differentiated voting elegibility thresholds applying in different elections in Germany, they analyze how first-time voters react when losing eligibility in a follow-up election. They exploit this setting in a difference-in-differences design using panel data. They find that temporary disenfranchisement decreases perceived external efficacy by 0.19 points on a five-point Likert scale and satisfaction with democracy by 0.14 points. Both results are statistically significant at the five-percent level. In contrast, internal efficacy and political interest remain unaffected by the treatment, and regaining voting eligibility is not associated with statistically significant changes in respondents' attitudes. This report focuses on the computational reproducibility and robustness replicability of these findings. To assess the paper's reproducibility, we first attempt to reproduce the paper's estimates and figures using the author's replication materials. In a second step, we perform several robustness checks by means of alternative difference-in-differences specifications using coarsened exact matching and entropy balancing, and a closer examination of panel attrition. Overall, we find complete reproducibility of the original replication materials. Our robustness checks confirm the sign congruence and significance of coefficients reported in the original paper. We raise the issue of potential bias due to differential panel attrition rates between treated and untreated respondents.
https://github.com/paugrau/2023_replication_montreal
Keywords: 330; Replication; Matching; Attrition